KAWASAN AGROWISATA BUAH NAGA DI PELAIHARI - Permadi, Imam; Heldiansyah, J.C (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Pelaihari has a lot of tourism potential, but the tour focuses more on natural beauty, so it requires a supporting tourist attraction, namely dragon fruit tourism. The design of Pelaihari Dragon Fruit Agrotourism is a great opportunity for the tourism sector to introduce more dragon fruit production in Pelaihari. The purpose of developing agro-tourism is to increase the diversity of tourism and increase the tourist attraction of Pelaihari. Tourism can be a means of recreation that provides comfort and education that provides teaching. By applying the metaphorical method to the design of building designs, educational recreational circulation, various interesting tourist rides that can provide visitors with a memorable experience.